Kembangkan Potensi Desa Hulawa, Laksanakan Program Peduli Bencana Geologi Sampai Program Pembuatan Tapal Batas - Permana, Aang Panji; Djamal Adi Nugroho Uno; Diwa Ahmad Luly; Ravit Tahuku (Politeknik Piksi Ganesha Indonesia, 2025)
The location of the community service implementation is in Hulawa Village located at the northern tip of Buntulia District, Pohuwato Regency, Gorontalo Province. Hulawa Village is located at the northern tip of Buntulia District, Pohuwato Regency is a place rich in natural beauty and abundant natural resources. Directly bordering Karya Indah Village, Bulangita Village in Paguat District, and Patilanggio District, this village exudes extraordinary charm from its surroundings. Regarding the development plan for Hulawa Village, students of Gorontalo State University implemented three waste cleanliness care programs consisting of making permanent trash bins, installing information boards and socializing waste care and waste recycling training. To achieve these goals in the implementation of the Merdeka Belajar Kampus Merdeka (MBKM) Real Work Lecture (KKN) activities, students from three faculties at Gorontalo State University used three stages of implementation procedures consisting of the preparation stage, the implementation stage and the final stage, namely finishing. The results of the implementation of community service from the three programs were successful with the support of the community. The installation of landslide-prone information boards in an effort to help the community to be careful in areas where information boards have been installed. For the creation of new trash bins can encourage the community to be aware of throwing trash in its place. While the creation of hamlet boundaries is useful for improving administrative order so as to provide clarity of the hamlet area.